Factors Influencing Safety Consciousness and Violations Among Licensed Drivers - Gultom, Zuli Agustina; Hazidar, Al Hamidy; Basri, Muhammad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The primary objective of this research was to identify and analyze the factors influencing driving safety in Medan city. By utilizing survey data as the primary source, the researchers sought to employ logistic regression analysis to uncover key determinants. The overarching goal was to gain insights into the specific factors, such as gender, latest education, safety drive, miscalculation, and violation, that significantly impact driving safety in the targeted area. Survey data served as the foundation for this research, with logistic regression employed as the analytical tool of choice. The data collected from drivers in Medan was meticulously examined to assess the influence of various factors on driving safety. The results of the analysis revealed several noteworthy findings regarding driving safety in Medan. Gender, latest education, safety drive, miscalculation, and violation emerged as significant factors affecting driving safety in the city. Notably, safety drives and violations were identified as particularly influential in determining the overall safety of driving in Medan. The majority of drivers in Medan possessed a driver’s license, with a significant proportion being teenagers. A correlation between driver’s license prediction and variables such as status and latest education was observed. However, age did not exhibit a significant correlation with driving miscalculations. These findings provide a foundation for the development of targeted driving safety programs in Medan, emphasizing the importance of awareness, reducing violations, and considering demographic factors like gender and recent education for effective safety driving strategies.